2004
DOI: 10.1111/j.1365-2842.2004.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between clinical oral health status and oral impacts experienced by older individuals in Sri Lanka

Abstract: The aim of this study was to determine the association between clinical oral status and oral impacts experienced by older individuals in Sri Lanka. A total of 585 individuals who were above 60 years and were residents of an urban area was selected using a multistage cluster sampling combined with probability proportionate to size technique. However the present analysis is limited to 235 individuals who were subjected to a clinical oral examination. An interviewer administered Sinhala translation of the Oral He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
6
28
1
Order By: Relevance
“…This is in agreement with McGrath & Bedi (2002) who concluded that effect of oral health on quality of life for the British population was considerable, with many individuals experiencing negative impacts across a broad range of physical, social and psychological aspects of life quality (20). An understanding and knowledge of the relationship between clinical and subjective indicators will enable the dental practitioner to make rational decisions about what oral conditions require treatment and the type of treatment that is needed for a given condition with the available resources (21).…”
Section: Discussionsupporting
confidence: 75%
“…This is in agreement with McGrath & Bedi (2002) who concluded that effect of oral health on quality of life for the British population was considerable, with many individuals experiencing negative impacts across a broad range of physical, social and psychological aspects of life quality (20). An understanding and knowledge of the relationship between clinical and subjective indicators will enable the dental practitioner to make rational decisions about what oral conditions require treatment and the type of treatment that is needed for a given condition with the available resources (21).…”
Section: Discussionsupporting
confidence: 75%
“…Several population surveys include 'number of teeth' in statistical models analyzing impact on OHRQoL, but this parameter appears not always to be the most prominent predictor. For example, in a population of older adults in Sri Lanka, Ekanayake [10] found only a weak association between tooth loss and other clinical parameters on the one hand and oral impacts on the other hand. This suggests that other factors such as age, gender or cultural background of the patient play an important role in the perception of health [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…More severe psychological or social limitations and handicap were not affected. Compared with other crosssectional studies, the impact of clinical data differs from strong predictor [25] to only weak, as reported by Ekanayake [26].…”
Section: Multivariate Analysismentioning
confidence: 63%